Pengembangan Modul Ajar Berbasis Kebhinekaan Menggunakan Model PBL (Problem Based Learning) pada Siswa Kelas VIII SMP Negeri 5 Peusangan Kabupaten Bireun - Yunazira, Yunazira; Astuti, Nia; Ariga, Hijrah Purnama Sari (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research aims to determine the development of a teaching module based on diversity using the PBL (problem Based Learning) model for eighth-grade students at SMP Negeri 5 Peusangan. The research method used is quantitative with an experimental approach, and the design applied is one group pretest and posttest. The research sample consists of 20 students. The data collection instrument is a test on speech materials before and after the treatment. Data analysis techniques are conducted through descriptive statistical tests, normality tests (Kolmogorov-Smirnov), hypothesis statistical tests or t-tests (Paired Sample Test), and N-Gain tests to see effectiveness. Before the treatment, the average score was 56.00, and after the treatment, the average score of students increased to 89.45, with the highest score being 100 from the assessment results of the speech text test using the diversity-based teaching module. This module not only enhances academic performance but also instills a sense of empathy, tolerance, and appreciation for the diversity of race, ethnicity, culture, and religion.